1988
DOI: 10.1016/0014-5793(88)80181-9
|View full text |Cite
|
Sign up to set email alerts
|

A cDNA clone encoding a 10.8 kDa photosystem I polypeptide of barley

Abstract: A cDNA clone encoding the barley photosystem I polypeptide which migrates with an apparent molecular mass of 16 kDa on SDS-polyacrylamide gels has been isolated. The 634 bp sequence of this clone has been determined and contains one large open reading frame coding for a 15 457 Da precursor polypeptide. The molecular mass of the mature polypeptide is 10 821 Da. The amino acid sequence of the transit peptide indicates that the polypeptide is routed towards the stroma side of the thylakoid membrane. The hydropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…6. Similarity between NH2-terminal regions of barley PSI-N and PSI-E and H. The amino acid sequences of PSI-E, and H were determined by [ 19,22]. Identical residues (solid line) and conservative substitutions (dotted line) are boxed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. Similarity between NH2-terminal regions of barley PSI-N and PSI-E and H. The amino acid sequences of PSI-E, and H were determined by [ 19,22]. Identical residues (solid line) and conservative substitutions (dotted line) are boxed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of most of the PSI subunits has been determined and most have been sequenced for barley [12,19,20,22,23,27]. Cross-linking, antibody inhibition and reconstitution studies have shown that PSI-D and PSI-E The nucleotide sequence data reported will appear in the EMBL, Genbank and DDBJ Nucleotide Sequence Databases under the accession number X66428.…”
Section: Introductionmentioning
confidence: 99%
“…Subunit IV, the product of the psaE gene, is also thought to be located on the stroma side of the thylakoids. It has been described in different higher plants [6,9] and Chlamydomonas [ …”
Section: Introductionmentioning
confidence: 99%
“…In cyanobacteria, however, neither a protein nor a gene corresponding to the iron-sulfur center-carrying component has been identified yet, although there are many functional and molecular biological indications of its presence [12][13][14]. The other core components of higher plants so far sequenced are all encoded by nuclear genome and their sequences vary considerably among plant species [15][16][17][18][19][20]. Some such core components from cyanobacteria have been also sequenced, but only one component has been proven to correspond to a higher plant homologue (subunit II or psaD product) [4,21,22].…”
Section: Introductionmentioning
confidence: 99%